The mice and the weasels: and other Aesop's fables - Parker, Vic , (Aesop's fables, 2013)
The text is young and simple, and clearly portrays helpful morals through fun characters that young readers can relate to. All of the classic, best-loved fables have been included, as well as some lesser-known stories that have been retold to intrigue and entertain children for the very first time.